1985
DOI: 10.3171/jns.1985.63.5.0704
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone and neurological function 1 year after spinal cord injury

Abstract: A multi-center double-blind randomized clinical trial was conducted by the National Acute Spinal Cord Injury Study Group to examine the efficacy of high-dose methylprednisolone (1000-mg bolus and 1000 mg daily thereafter for 10 days) compared with that of a standard dose (100-mg bolus and 100 mg daily for 10 days). No significant difference was observed in neurological recovery of motor function, pinprick response, or touch sensation 1 year after injury between the two treatment groups, after adjustment for ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0
6

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(115 citation statements)
references
References 13 publications
0
109
0
6
Order By: Relevance
“…High V1. 4 Fund work that exploits the insights generated by V1.2 to determine the scope and e ectiveness of harnessing the natural regulators of trauma, in¯ammation and scar formation after SCI, again assessing the outcome by its bene®cial impact on subsequent nerve regeneration rather than on the tissue disruption per se.…”
Section: V13mentioning
confidence: 99%
See 1 more Smart Citation
“…High V1. 4 Fund work that exploits the insights generated by V1.2 to determine the scope and e ectiveness of harnessing the natural regulators of trauma, in¯ammation and scar formation after SCI, again assessing the outcome by its bene®cial impact on subsequent nerve regeneration rather than on the tissue disruption per se.…”
Section: V13mentioning
confidence: 99%
“…1,4 Experimental studies in adult rats have shown methylprednisolone treatment to reduce lesion size, 5 increase the percentage of spared tissue and restore neurological function, 6 improve locomotor recovery 7 and increase axonal regeneration across Schwann cell grafts. 8 Methylprednisolone treatment combined with delivery of basic ®broblast growth factor was found to have additive bene®cial e ects on reversing neurological de®cits.…”
Section: Proposed Approachmentioning
confidence: 99%
“…[1][2][3][4] However, its use is also associated with a significant increase in complications related to systemic immunosuppression. Specifically, the incidence of wound infection, sepsis, pneumonia, and the duration of intensive care unit stay are all increased in patients receiving high-dose methylprednisolone.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In order to demonstrate the ine ectiveness of corticosteroids, a randomized controlled study was conducted by the National Acute Spinal Cord Injury Study group (NASCIS-1). 4 The treatment group received a 1000 mg bolus of methylprednisolone (Mpred) with 1000 mg daily for 10 days, while the control group was given a 100 mg bolus with 100 mg daily for 10 days. There was no signi®cant di erence in neurologic outcome between the two groups.…”
Section: Introductionmentioning
confidence: 99%